Tipi ektomikorize pri sadikah bukve (Fagus sylvatica L.) v rizotronih - Štraus, Ines (Zbornik gozdarstva in lesarstva, 2011)
Natural processes or human activities affect environmental conditions, as reflected in the structure of the communities and the level of ectomycorrhizalfungi. The aim of the study was to determine the potential impacts of several temperature regimes of air and soil (substrate) on the occurrence and species diversity of ectomycorrhizal fungi in symbiosis and in the substrate. For this purpose, we analyzed the occurrence of types of ectomycorrhizae on beech seedlings in rhizotrons exposed to four different environmental temperature conditions: 1) air 15-25°C, 2) air 15-25°C in combination with cooling of roots for 5°C, 3) elevated air temperature from 30-50°C, and 4) ambiental conditions (air temperature in Ljubljana). Types of ectomycorrhizae were identified with a combined approach of anatomical morphological characterisation and with analysis of molecular markers (ITS1-5.8S rDNA-ITS2 ribosomal region in rDNA). We identified a total of 6 types of ectomycorrhizae on 51 root tips on 40 beech seedlings. The diversity of ectomycorrhizal types was the highest in terms of near-optimal growth conditions of beech. Most similar as far as species diversity of ectomycorrhizal fungi are concerned were the experiments with air temperature of 15-25°C with or without cooling of the root system. The commonest ectomycorrhizal species was Hebeloma sacchariolens, which was also the most commonly seen species in fine roots of dead plants. Selected species of ectomycorrhizal fungi were further substantiated with DGGE method in all analyzed substrate samples.
Keywords: bukev; ektomikoriza; Fagus Sylvatica L.; filogenija; markerji; vpliv temperature